2017
DOI: 10.18203/2319-2003.ijbcp20175206
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of self-medication practice among undergraduate medical students of tertiary care hospital, Andhra Pradesh, India

Abstract: Background: According to World Health Organization resources, Selfmedication is selection and use of drugs to treat self-diagnosed disorders or symptoms which includes the usage of non-prescription drugs. It is widely seen among undergraduate students especially in developing countries like India. Our objective of the study is to know the pattern of self-medication practice among undergraduate medicos in medical college attached to tertiary care hospital. Methods: This is a Prospective, cross-sectional, questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…This result is consistent with other similar studies of health science students in Ethiopian higher educational institutions such as Arsi University, 33 University of Gondar, 37,68 Private Health Science Colleges in Gondar, 69 and Mekelle University. 70 There are also confirming reports from Bahrain, 22 Eritrea, 39 Saudi Arabia, 71 and India 30,53,62 on the frequently used SM groups and perceived disease conditions. Similarly, analgesics and antibiotics were the two foremost self-medicated drugs in Nigerian students, 72 whereas non-steroidal analgesic, anti-inflammatory, and antipyretic drugs were the most frequently used OTC drugs for self-treating fever and headaches in Nepal.…”
Section: Attitude Towards Self-medication and Associated Factorsmentioning
confidence: 56%
See 1 more Smart Citation
“…This result is consistent with other similar studies of health science students in Ethiopian higher educational institutions such as Arsi University, 33 University of Gondar, 37,68 Private Health Science Colleges in Gondar, 69 and Mekelle University. 70 There are also confirming reports from Bahrain, 22 Eritrea, 39 Saudi Arabia, 71 and India 30,53,62 on the frequently used SM groups and perceived disease conditions. Similarly, analgesics and antibiotics were the two foremost self-medicated drugs in Nigerian students, 72 whereas non-steroidal analgesic, anti-inflammatory, and antipyretic drugs were the most frequently used OTC drugs for self-treating fever and headaches in Nepal.…”
Section: Attitude Towards Self-medication and Associated Factorsmentioning
confidence: 56%
“…This is nearly similar with the investigation in India, where 52.9% of undergraduate health science students in a tertiary care hospital confidently prescribed medicines on their own to themselves, their friends, and family members. 62 The belief of self-diagnosis and self-treatment is not limited only to the developing countries, but it is also prevalent in developed western regions with various degrees of prevalence. Earlier study reports revealed that 39.2% of the health science students in the United Kingdom 45 and about 22% of health students in the USA 44 agreed on the appropriateness of self-prescribing.…”
Section: Attitude Towards Self-medication and Associated Factorsmentioning
confidence: 99%